2019
DOI: 10.1016/j.biombioe.2019.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Layer formation on K-feldspar in fluidized bed combustion and gasification of bark and chicken manure

Abstract: Layer formation on K-feldspar in fluidized bed combustion and gasification of bark and chicken manure, Biomass and Bioenergy. 127 (2019) 105251.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Furthermore, the utilization of residual biomass of lower quality than stem-wood-based biomass is of high interest for improving the economic feasibility of the process as well as increasing the share of renewables in the energy mix. Previous studies have been focused on the use of, e.g., chicken manure, bark, straw, sugar cane bagasse, or exhausted olive pomace as residual biomass [21][22][23]. Different residual biomasses cannot be compared easily since their composition and fuel characteristics vary greatly.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the utilization of residual biomass of lower quality than stem-wood-based biomass is of high interest for improving the economic feasibility of the process as well as increasing the share of renewables in the energy mix. Previous studies have been focused on the use of, e.g., chicken manure, bark, straw, sugar cane bagasse, or exhausted olive pomace as residual biomass [21][22][23]. Different residual biomasses cannot be compared easily since their composition and fuel characteristics vary greatly.…”
Section: Introductionmentioning
confidence: 99%
“…While studies referring to industrial-scale plants mainly focused on olivine as a bed material [26], several alternative bed materials have been studied in lab-to pilot-scale experiments, where an activation could be observed [16,17,27,28]. Studies have shown that the layer formation during (steam) gasification is comparable to layer formation during combustion [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the observed problems of agglomeration and deposition formation with quartz beds [7,16,17], several alternative bed materials, like olivine [6], K-feldspar [6], magnesite [17][18][19], calcite [18,19], dolomite [17], sillimanite [18], bauxite [18], and plagioclase [6], were tested for their suitability in fluidized bed applications. Further studies on K-feldspar focused on the layer formation in combustion [14] and gasification atmosphere [12], or a direct comparison of both [20]. Berguerand and Berdugo Vilches tested Alkali-feldspar (a mixture of K-and Na-feldspar with impurities of Ca-feldspar) in the Chalmers 2 MW indirect gasifier as bed material for gasification applications with wood.…”
Section: Introductionmentioning
confidence: 99%
“…For a quartz bed, changes in ash chemistry based on phosphorus content could be observed in the gas phase [23] and through its influences on bed agglomeration tendencies [4]. Phosphorus-rich fuels were tested in a gasifier and in combustion atmosphere in combination with K-feldspar [20,22] also giving a first proposal regarding a possible layer forming mechanism on K-feldspar. Further, the importance of phosphorus as a nutrient is recognized among the planetary boundaries along with eight other criteria [24].…”
Section: Introductionmentioning
confidence: 99%